Heat-insulating mortar based on composite binder - D. A. Sumskoi (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2018)
The article presents the results of studies on obtaining a heat-insulating solution obtained by grinding. The binding compositions were synthesized at various ratios of cement and waste products of perlite sand in ajet mill under different grinding regimes. The features of grinding processes have been studied and technological and physicomechanical properties of the resulting binding compositions have been determined. The microstructure of cement stones obtained from activated Portland cement and binding compositions in ajet mill was studied by electron microscopy. It is established that open pores of cement-binding compositions prepared using perlitic fillers are filled with neoplasms and perlite grains have a plate-prismatic shape, which is clearly seen in micrographs. The microstructure of binding compositions has a dense structure due to a rationally selected composition, the use of an effective mineral filler, which creates additional substrates to form the internal microstructure of the composite. A comparative X-ray diffraction analysis of hydrated plain cement and binding composition was carried out and it was established that hydrated cement and binding composition are identical in mineral composition, having Ca hydroalumates, Ca (OH)2, CSH, and low amounts of ettringite. A distinctive feature of the diffractograms is the significant amorphization of the binding composition. The range of the optimal ratio of cement to perlite was found to be 1:9; 1:11; 1:13. A heat-insulating solution based on composite binder and expanded perlite aggregate (1:11) with a density of 1200 kg / m3 and a strength of 2.5 MPa was obtained. Modification of the solution by additives of superplasticizer; blowing agent; redispersible dispersion powder, it was possible to obtain a heat-insulating solution with a density of 973.11 kg/m3. Optimization of this solution with expanded polystyrene microspheres made it possible to obtain a density of the composite of 240-260 kg/m3 at a compressive strength of 1.05-1.15 MPa. The developed heat-insulating compounds have a reduced density and sufficient strength, which is the reason to recommend them for use in the manufacture of construction works.